Hubungan Antara Kualitas Pelayanan Tenaga Kesehatan Dengan Kepuasan Dan Loyalitas Pasien Rawat Jalan Dan Rawat Inap Di Rs Pku Muhammadiyah Bantul Yogyakarta - Sari, Aji Hidayah Dayang, Dr. dr H. Iwan Setiawan Adji, Sp.THTKL, Dr. Amin Mustofa, Sp.Ak MARS (2017)
This research aims to identify and analyze the correlation of: 1) the quality service to satisfaction. 2) quality of service to patient loyalty. 3) patient satisfaction to patient loyalty. The data of this research is the premier data which was obtained from the answers of 100 respondents. Data analysis tools using path analysis (path analysis). The test results concluded that all variables instrument valid and reliable as a data collection tool. In the data analysis shows that: 1) the service quality has significant and positive correlation on patient satisfaction. 2) The service quality has not significant and positive correlation on patient loyalty. 3) the service quality has significant and positive correlation on patient satisfaction and patient loyalty